ABNORMAL CASEO OF STRESS CORROSION CRACKING (Perner's Contacts, 2022)
In this paper are shown two atypical cases of stress corrosion cracking of iron alloys. Austenitic stainless steel 1.4404 (ASTM 316L) was exposed to exhaust gas after the combustion of pulverized coal in a fluidized bed furnace. Corrosion was initiated by residual stresses after cold forming. Steel 1.2343 was used to manufacture of an aluminum casting die. Here, corrosion was initiated on the surface of the cooling channel. In the cooling circuit, treated water was used by corrosion inhibitors addition and pH 8 to 9. In both cases, surface contamination or inhomogeneity of the material composition was not found. These chemical composition inhomogeneities might usually explain the causes of corrosion. In both cases, the growth of the corrosion cracks was very rapid. Due to the fact that in both cases the crack initiation originated in places with a significant stress in the material, it is reasonable to assume damage by the stress corrosion cracking mechanism.
Keywords: Stress Corrosion Cracking; Austenitic Steel; Tool Steel; Microstructure; Residual Stress; SEM